2022
DOI: 10.33596/coll.86
|View full text |Cite
|
Sign up to set email alerts
|

Adaptations of an RCT during COVID: Case Study in one Rural American Indian Community

Abstract: The COVID-19 pandemic is global in nature but especially threatens American Indian and Alaska Native (AI/AN) communities due to pre-existing conditions and social determinants of health. Because of the higher risk to AI/AN communities, many tribal nations have been proactive in their policies to keep the virus at bay, including travel restrictions and lockdowns. This affected tribal programs as well as collaborative research projects. One project impacted is the Native CHOICES project, an ongoing randomized co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…Although our study did not show differences among vaccination status in micropolitan versus metropolitan areas, this study did find that individuals who resided in metropolitan areas were less concerned about the COVID-19 vaccine side effects. Studies have shown that metropolitan areas are associated with higher vaccination rates compared to micropolitan areas due to variables, such as better healthcare infrastructure, accessibility to vaccination sites, and differences in socioeconomic status and education levels [53,54]. Recognizing these unique challenges is critical in implementing effective interventions in rural and micropolitan areas.…”
Section: Place Of Residencementioning
confidence: 99%
“…Although our study did not show differences among vaccination status in micropolitan versus metropolitan areas, this study did find that individuals who resided in metropolitan areas were less concerned about the COVID-19 vaccine side effects. Studies have shown that metropolitan areas are associated with higher vaccination rates compared to micropolitan areas due to variables, such as better healthcare infrastructure, accessibility to vaccination sites, and differences in socioeconomic status and education levels [53,54]. Recognizing these unique challenges is critical in implementing effective interventions in rural and micropolitan areas.…”
Section: Place Of Residencementioning
confidence: 99%
“…Many AIAN communities have been disproportionately affected by the pandemic, 8 and many tribal nations imposed strict regulations to prevent the spread of disease. 9 Our group successfully implemented Native CHOICES, a prevention study, in tribal communities that employed a broad range of strategies to reduce the spread of COVID-19, including checkpoints on vehicular traffic, residential curfews, reductions in community services, and targeted stay-at-home orders. 9 The principles of CBPR, as outlined by Israel et al, 10 that will be most prominently featured in this study, are the recognition of the community as a unit of identity, an effort to build on the strengths and resources already present within the community, a collaborative partnership between the university, the research organization, the Native community in all phases of the research, and a cyclical and incremental process throughout the changes implemented in the study.…”
Section: Introductionmentioning
confidence: 99%
“…We provide a fuller discussion of our adaptations in a separate publication. 9 The goal of the present article is to use a project timeline and qualitative data from field staff to highlight the essential role of community engagement in successful study recruitment during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%